Exploring the Role of Teachers in Shaping Student Character in Schools: A Managerial Perspective - Umam, Khoirul; Ahmad Fauzi; Ummi Lailia Maghfiroh (Journal of Educational Management Research, 2025)
This study examines the role of Islamic Religious Education (PAI) teachers in shaping students’ character in schools, primarily through their roles, namely as leaders, educators, motivators, and evaluators. This study was conducted using a qualitative approach, collecting data through in-depth interviews, observations, and documentation in the school environment. Data analysis was done through data display, reduction, and conclusions drawing. The results of the study indicate that PAI teachers act as leaders who create an active and Islamic learning atmosphere and are role models for students. As motivators, teachers succeed in raising students’ enthusiasm to innovate and practice religious values ​​in everyday life. In addition, PAI teachers also play the role of evaluators by providing holistic assessments, covering aspects of knowledge, attitudes, skills, and spirituality, which help monitor the development of students’ character. This study provides an important contribution to renewing perspectives on the role of teachers in character education, especially in the context of Islamic religious education. Although these findings indicate success in character formation, external challenges, such as the influence of family and peers, continue to influence the implementation of the values ​​taught.